Association between human cytomegalovirus related factors and development of the disease in renal and bone marrow transplant recipients in a tertiary hospital, Malaysia - Mastuki, Mohd Fahmi (2014)
Human cytomegalovirus (HCMV) infection is known to be a major infectious complication after transplantation which associated with significant morbidity and mortality in solid organ and bone marrow transplant recipients. We studied the viral factors of HCMV and correlate results with the development of HCMV disease. This aim of this study is to detect HCMV, their genotypes and co-infection with other herpesviruses namely Epstein-Barr virus (EBV), Human herpesvirus 6 (HHV-6) and Human herpesvirus 7 (HHV-7) in post-solid organ and bone marrow transplant recipients and to correlate them with the clinical presentation and outcome of HCMV disease. In this study, 100 blood samples from renal transplant recipients and 100 bone marrow transplant recipients in Kuala Lumpur Hospital were included. All tests were carried out by real time polymerase chain reaction (qPCR). HCMV were detected in higher incidence compared to other herpes virus indicating that the virus was the most common virus infecting the immunosuppressed patients. The results revealed that the incidence of HCMV infection were 78% and 63% in renal and bone marrow transplant recipients respectively. We found that patients with high viral load show symptoms of HCMV disease, whereby fever being most common symptom. As Malaysia has multi-races citizens, we also demonstrate the incidence of HCMV infection among renal and bone marrow transplant recipients by ethnicity namely Malay, Chinese, Indian and other minority races as ‘others’. In renal transplant recipients, there was no significant difference between the ethnic. Nevertheless, we found that there was a significant HCMV positivity among races in bone marrow transplant recipients where Malays were the most infected. One of the pathogenesis of HCMV depends on the genes encoding envelope glycoprotein that associated with different clinical outcomes. Reactivation of latent viral infection by HCMV and other herpesviruses results in active viral infection after organ transplantation and may cause complications. HCMV genotyping analysis revealed that all three HCMV gB, gH and gN genotypes were presence in the population where gB1 strain being the most common gene detected in both renal (100%) and bone marrow (100%) transplant recipients. Mix infection by more than one HCMV genotypes was also detected with various percentages with the gB+gH+gN combination was the least type of mix infection. We also found that recipient with high HCMV viral load (>5,000 copies/mL) has increased risk of developing HCMV disease. No statistically significant difference was found between type of genotypes and the manifestation of HCMV disease (p>0.05). Co-infection with other herpesviruses with HCMV disease was significant in bone marrow transplant recipients but not significant in renal transplant recipient.